Drinking patterns of adolescents who develop alcohol use disorders: results from the Victorian Adolescent Health Cohort Study - Olsson, Craig A (BMJ Open, 2016)
OBJECTIVE: We identify drinking styles that place teens at greatest risk of later alcohol use disorders (AUD). DESIGN: Population-based cohort study. SETTING: Victoria, Australia. PARTICIPANTS: A representative sample of 1943 adolescents living in Victoria in 1992. OUTCOME MEASURES: Teen drinking was assessed at 6 monthly intervals (5 waves) between mean ages 14.9 and 17.4 years and summarised across waves as none, one, or two or more waves of: (1) frequent drinking (3+ days in the past week), (2) loss of control over drinking (difficulty stopping, amnesia), (3) binge drinking (5+ standard drinks in a day) and (4) heavy binge drinking (20+ and 11+ standard drinks in a day for males and females, respectively). Young Adult Alcohol Use Disorder (AUD) was assessed at 3 yearly intervals (3 waves) across the 20s (mean ages 20.7 through 29.1 years). RESULTS: We show that patterns of teen drinking characterised by loss of control increase risk for AUD across young adulthood: loss of control over drinking (one wave OR 1.4, 95% CI 1.1 to 1.8; two or more waves OR 1.9, CI 1.4 to 2.7); binge drinking (one wave OR 1.7, CI 1.3 to 2.3; two or more waves OR 2.0, CI 1.5 to 2.6), and heavy binge drinking (one wave OR 2.0, CI 1.4 to 2.8; two or more waves OR 2.3, CI 1.6 to 3.4). This is not so for frequent drinking, which was unrelated to later AUD. Although drinking was more common in males, there was no evidence of sex differences in risk relationships. CONCLUSIONS: Our results extend previous work by showing that patterns of drinking that represent loss of control over alcohol consumption (however expressed) are important targets for intervention. In addition to current policies that may reduce overall consumption, emphasising prevention of more extreme teenage bouts of alcohol consumption appears warranted.